The role of knowledge management strategies in building core competenciesAn exploratory study of the views of a sample of managersOffice of Financial Supervision in Iraq - الكبيسي, صلاح الدين عواد; ياسين, مهند محمد (Journal of Economics and Administrative Sciences, 2011)
The strategies of knowledge management have became the basis in the promotion of core competencies. Therefore gained an increasing prominence. This led the administrations of organizations to work to effectiveness of there strategies, which results to build there core competences through teamwork, empowerment and personal effectiveness of employees. From this arises research problem about the  organizations leaders recognize extent of knowledge management strategies which that lead to core competence. In addition the research tray definition the relation and nature of affect between its variables. The research was carried on sample (72) managers from board of supreme audit in Iraq and used statistical tools and methods.The major results are: the codification strategy relation and effect in significance with core competence in individual and gross levels. But the personalization strategy relation and effect with core